THE INSTRUMENT ANALYSIS OF STUDENTS COGNITIVE SKILL ON SOLAR SYSTEM TOPICS - Deby Cintia; Rahmah Evita Putri (Universe, 2021)
This study aims to obtain a valid, reliable, and quality cognitive ability instrument in the material of the Solar System Class VII SMPN 1 Solok Selatan. This research is descriptive (Descriptive Research) quantitative approach. The population of this study was class VIII and IX at SMP Negeri 1 Solok Selatan which were registered in the 2020/2021 school year. Sampling using purposive sampling technique. The research data used is in the form of primary data, namely data that is collected directly from the sample studied using the instrument. The research data were analyzed by using expert validity analysis, reliability analysis, distinguishing power analysis and problem difficulty level analysis. The results of validity by expert validators found that 50 items in the form of multiple choice were categorized as valid. Based on the Reliability Analysis, it was found that the questions were reliable. The question instrument with the analysis of the distinguishing power of the questions obtained the results of 16 items with the valid and suitable category for use. Based on the Problem Difficulty Level analysis, the results were obtained with moderate criteria, so that a valid, reliable and quality instrument was obtained to measure the cognitive abilities of students.